2020
DOI: 10.3390/ijms21051576
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor Increases SIRT1 and HES1 mRNA Levels in Peripheral Blood Cells from Patients with Stable Coronary Artery Disease and Chronic Obstructive Pulmonary Disease

Abstract: Ticagrelor is a powerful P2Y12 inhibitor with pleiotropic effects in the cardiovascular system. Consistently, we have reported that in patients with stable coronary artery disease (CAD) and concomitant chronic obstructive pulmonary disease (COPD) who underwent percutaneous coronary intervention (PCI), 1-month treatment with ticagrelor was superior in improving biological markers of endothelial function, compared with clopidogrel. The objective of this study was to investigate the mechanisms underlying these be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…Previous studies in patients with stable coronary artery disease and chronic inflammation due to chronic obstructive pulmonary disease showed that treatment with ticagrelor improved surrogate markers of endothelial function, mediated by induction of the SIR1/HES1 (sirtuin 1/hairy and enhancer of split 1) axis in reducing EGF, independent of an antiplatelet effect. 21,34 It is possible that ticagrelor exhibits a more prominent effect on EGF level in those patients with underlying chronic inflammation, and thus no significant treatment effect was observed in this study. Similarly, the lack of treatment effects of ticagrelor on platelet activation, circulating EPC, and IL-6 as reported in other studies 15,16 may be attributed to the low baseline levels of platelet activation and inflammation in our study population.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies in patients with stable coronary artery disease and chronic inflammation due to chronic obstructive pulmonary disease showed that treatment with ticagrelor improved surrogate markers of endothelial function, mediated by induction of the SIR1/HES1 (sirtuin 1/hairy and enhancer of split 1) axis in reducing EGF, independent of an antiplatelet effect. 21,34 It is possible that ticagrelor exhibits a more prominent effect on EGF level in those patients with underlying chronic inflammation, and thus no significant treatment effect was observed in this study. Similarly, the lack of treatment effects of ticagrelor on platelet activation, circulating EPC, and IL-6 as reported in other studies 15,16 may be attributed to the low baseline levels of platelet activation and inflammation in our study population.…”
Section: Discussionmentioning
confidence: 80%
“…Krishnan et al [133], Hu et al [134], Martins et al [135], Prieto-Sánchez et al [136], Sugulle et al [137], Zhao et al [138], Siddiqui et al [139], Han et al [140], Lappas et al [141], Wang et al [142], Artunc-Ulkumen et al [143], Blois et al [144], Vacínová et al [145] and Vilmi-Kerälä et al [146] demonstrated that the expression of CREBRF (CREB3 regulatory factor), STRA6, EGFR (epidermal growth factor receptor), MFSD2A, GDF15, PAK1, VCAM1, IGFBP2, IGFBP7, PRKCA (protein kinase C alpha), ADAMTS9, LGALS1, BIN1, TIMP1 and are associated with progression of GDM. Aquila et al, [147],Chen et al [148], Xie et al [149], Zhang et al [150], Aspit et al [151], Akadam-Teker et al [152], Jiang et al [153], Cetinkaya et al [154], Grond-Ginsbach et al [155], Dong et al [156], Chardon et al [157], Chen et al [158], Yamada et al [159], Hu et al [160], Bobik and Kalinina [161], Schwanekamp et al [162], Liu et al [163], Schroer et al [164], Raza et al [165], Yang et al [166], Azuaje et al [167], Durbin et al [168], Chowdhury et al [169], Wang et al [170], Li et al [171], Lv et al [172], Bertoli-Avella et al [173], Grossman et al [174], Andenæs et al [175] and Chen et al [176] demonstrated that HES1, SPIN1, TBX3, EVA1A, CAP2, BMP1, HSPB8, RDX (radixin), COL5A1, LIMS2, PARVA (parvin alpha), EGFLAM (EGF like, fibronectin type III and laminin G domains), NEXN (nexilin F-actin binding protein), TNFRSF14, TGFBI (transforming growth factor beta induced), HAVCR2, CDH11, COL4A1, COL4A2, COL5A2, SHROOM3, HYAL2, PDLIM3, ETS2, PLSCR4, TGFB3, COL6A2 and LTBP2 could induce cardiovascular diseases, but these genes might be essential for progression of GDM. Flamant et al [177], Wan et al [178], Zhang et al [179], Vallvé et al [180], Heximer and Husain [181], Selvarajah et al [182], Jain et al [183], Sun et al [184], Satomi-Kobayashi et al [185], Jiang et al [186], Waghulde et al [187] and Dahal et al [188] reported that DDR1, CAST (calpastatin), KYNU (kynureninas...…”
Section: Discussionmentioning
confidence: 99%
“…Serum of ticagrelor-treated patients was found to increase eNOS levels of HUVEC [ 212 ]. Shortly afterwards, peripheral blood cells from CAD patients with concomitant chronic obstructive pulmonary disease treated with ticagrelor showed decreased SIRT1 and HEAS1 mRNA expression (anti-inflammatory genes), which correlated negatively with EGF serum levels [ 213 ].…”
Section: Biomarkersmentioning
confidence: 99%